Fast Course for Authors: how to write a paper - Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif]--> HTML clipboard <!-- span.MsoEndnoteReference {vertical-align:super} span.subhead1 {font-family:Verdana; font-weight:bold} span.MsoFootnoteReference {vertical-align:super} table.MsoTableGrid {border:1.0pt solid windowtext; font-size:10.0pt; font-family:"Times New Roman"} li.MsoNormal {mso-style-parent:""; margin-bottom:.0001pt; font-size:12.0pt; font-family:"Times New Roman"; margin-left:0cm; margin-right:0cm; margin-top:0cm} table.MsoTable3DFx2 {font-size:10.0pt; font-family:"Times New Roman"; } table.MsoTableColorful1 {border:1.5pt solid teal; font-size:10.0pt; font-family:"Times New Roman"; color:white; } --> PROBLEM: the authors fail to write a manuscript in a way that is accessible to readers of a general journal. OBJECTIVE: Point out that scientific manuscripts published by OBJN must follow the IMRaD style (introduction, methods, results and discussion) or DMPAEP and should have a structured abstract and a structured discussion. METHOD: Fast class about writing a manuscript. CONCLUSION: The OBJN argues for including "writing for publication" as subject of the research methodology nursing discipline.